Kuliah Kerja Nyata: Digitalisasi Pemasaran UMKM Di Desa Tegur Wangi Lama - Nurmaleni, Nurmaleni; Rahayu, Chika; Kasman, Kasman (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
The people of the village are on average engaged as vegetable farmers, in some areas they are also salak fruit farmers. MSMEs in the community certainly still use the traditional sale of vegetables and fruits to the city center or traditional markets. able to fill community activities to increase independent income or village apparatus.Salak fruit can be very helpful when farmers cannot maximize land when planting vegetables due to climatic factors. Salak fruit can be sold to souvenir traders and traders along the old village road. Vegetable dumplings in the form of wartels and spinach are maximized from vegetable processing, processed products in the form of 'Healthy snack dumplings'. The research method uses qualitative and collects all information with other journals. The community is expected to apply this knowledge regularly, provide activities to the community and to youth-I to take advantage of digitalization by making healthy snacks from vegetables to being able to sell products through social media or digital.